Risk of major amputation in patients with intermittent claudication undergoing early revascularization. Issue 6 (22nd March 2018) - Golledge, J; Moxon, J V; Rowbotham, S; Pinchbeck, J; Yip, L; Velu, R; Quigley, F; Jenkins, J; Morris, D R
Abstract: Background: Revascularization is being used increasingly for the treatment of intermittent claudication and yet few studies have reported the long-term outcomes of this strategy. The aim of this study was to compare the long-term outcome of patients with intermittent claudication who underwent revascularization compared with a group initially treated without revascularization. Methods: Patients with symptoms of intermittent claudication and a diagnosis of peripheral arterial disease were recruited from outpatient clinics at three hospitals in Queensland, Australia. Based on variation in the practices of different vascular specialists, patients were either treated by early revascularization or received initial conservative treatment. Patients were followed in outpatient clinics using linked hospital admission record data. The primary outcome was the requirement for major amputation. Kaplan–Meier curves, Cox regression and competing risks analyses were used to compare major amputation rates. Results: Some 456 patients were recruited; 178 (39·0 per cent) underwent early revascularization and 278 (61·0 per cent) had initial conservative treatment. Patients were followed for a mean(s.d.) of 5·00(3·37) years. The estimated 5-year major amputation rate was 6·2 and 0·7 per cent in patients undergoing early revascularization and initial conservative treatment respectively ( P = 0·003). Early revascularization was associated with an increased requirement for major amputation in models adjusted for other risk factors (relative risk 5·40 to 4·22 in different models). Conclusion: Patients presenting with intermittent claudication who underwent early revascularization appeared to be at higher risk of amputation than those who had initial conservative treatment. Abstract : Early revascularization associated with amputation